Huecas tradicionales y el desarrollo del turismo gastronómico de la ciudad de Babahoyo - Coello Tuarez Maria Fernanda (2024)
This project focuses on traditional Huecas and the development of gastronomic tourism in the city of Babahoyo. Tourism is a great attraction for many people and paves the way for the development of the city. The methodology applied is mixed and descriptive. In addition, a large number of existing wells were identified within the city of Babahoyo, of which 10 were selected as a sample for the investigation; The technical sheets addressed to each owner served as an instrument for data collection. The purpose was to propose a gastronomic tour in Babahoyo that uses the local ravine as a theme to boost tourism. We were able to find a total of 20 holes. The oldest ones, like Salas y Sanduches Don Panchito, have strong ties with locals and even tourists, indicating that, in the gastronomy business, tradition and quality are key factors for the sustained success of an establishment. Therefore, it is recommended to regularize the permits of tourist accommodation establishments to strengthen credibility and guarantee quality standards for all tourists who visit the city of Babahoyo, especially these places; as well as suggested during your stay in these places.